Actin-mediated plasma membrane plasticity of the intracellular parasite Theileria annulata - Kühni‐Boghenbor, Kathrin; Lemgruber, Leandro; Cyrklaff, Marek; Frischknecht, Friedrich (Cellular microbiology, 2012)
Pathogen-host interactions are modulated at multiple levels by both the pathogen and the host cell. Modulation of host cell functions is particularly intriguing in the case of the intracellular Theileria parasite, which resides as a multinucleated schizont free in the cytosol of the host cell. Direct contact between the schizont plasma membrane and the cytoplasm enables the parasite to affect the function of host cell proteins through direct interaction or through the secretion of regulators. Structure and dynamics of the schizont plasma membrane are poorly understood and whether schizont membrane dynamics contribute to parasite propagation is not known. Here we show that the intracellular Theileria schizont can dynamically change its shape by actively extending filamentous membrane protrusions. We found that isolated schizonts bound monomeric tubulin and in vitro polymerized microtubules, and monomeric tubulin polymerized into dense assemblies at the parasite surface. However, we established that isolated Theileria schizonts free of host cell microtubules maintained a lobular morphology and extended filamentous protrusions, demonstrating that host microtubules are dispensable both forthe maintenance of lobular schizont morphology and for the generation of membrane protrusions. These protrusions resemble nanotubes and extend in an actin polymerization-dependent manner; using cryo-electron tomography, we detected thin actin filaments beneath these protrusions, indicating that their extension is driven by schizont actin polymerization. Thus the membrane of the schizont and its underlying actin cytoskeleton possess intrinsic activity for shape control and likely function as a peri-organelle to interact with and manipulate host cell components.
Gesehen am 27.11.2018